PENGALAMAN ODHA DALAM MENGHADAPI STIGMA DAN DISKRIMINASI TERKAIT PENYAKITNYA - Wenny Nugrahati Carsita (The Indonesian Journal of Health Science, 2017)
HIV AIDS is a global problem where every country reports that HIV AIDS is the greatest health challenge. In Indonesia, the number of people living with HIV AIDS  (PLWHA)  from  year  to  year  is  increasing.  HIV  AIDS  disease  affects physical and psychosocial problems where one of the causes is stigma and discrimination. Stigma and discrimination have a negative impact on the life of PLWHA including health behavior. The aim of this study is to explore the experience of PLWHA in the face of stigma and discrimination related to the disease. This study used a qualitative research design using interpretive phenomenological approach. Data were collected by in-depth interviews in 6PLWHA who were able to express their experiences and were willing to be participants. The results were analyzed by Van Manen method. Five themes were identified in this study namely: (1) Suffering from a scary disease (2) Avoided (3) Experiencing negative emotional response (4) Want to be accepted (5) Ignoring stigma and discrimination. The experience of PLWHA in the face of stigma and discrimination effect misery and hope for PLWHA. All the processes faced by PLWHA in the form of suffering scary disease and avoidance generate negative emotional response. The negative emotional response experienced by the PLWHA raises hope that PLWHA can be accepted although the attitudes and actions done by PLWHA is avoided. It is hoped for health workers to increase promotive efforts through AIDS education activities to minimize stigma and discrimination in PLWHA,  and  the  health  workers  also  understanding  about  the  suffering  of PLWHA not limited to physical problems due to illness, but also psychological and social consequences of stigma and discrimination. Keywords: experience, PLWHA, stigma, discrimination.